2017
DOI: 10.1111/ijlh.12751
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological feature of bone marrow granulomas: A modern Australian series

Abstract: Marrow granulomas are seen in a variety conditions. Neither their presence nor their morphological features are a guide to further investigations, which should be determined by the clinical presentation as appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…However, in half of these 10 patients the BMB finding was granulomatous involvement. This feature in itself is not diagnostic, as granulomata are non‐specific and may be observed in the bone marrow in several conditions, including infection, malignancy and autoimmune diseases, which are all differential diagnoses in a patient with FUO . Furthermore, the morphological appearance of the granulomata also do not guide further investigation, which is dependent on other clinical features and laboratory and imaging investigations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in half of these 10 patients the BMB finding was granulomatous involvement. This feature in itself is not diagnostic, as granulomata are non‐specific and may be observed in the bone marrow in several conditions, including infection, malignancy and autoimmune diseases, which are all differential diagnoses in a patient with FUO . Furthermore, the morphological appearance of the granulomata also do not guide further investigation, which is dependent on other clinical features and laboratory and imaging investigations …”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, the morphological appearance of the granulomata also do not guide further investigation, which is dependent on other clinical features and laboratory and imaging investigations. 10 BMB has been shown to be useful in the diagnosis of malignancy and infection. 2,3 In our cohort, BMB conferred a diagnosis of malignancy in five patients, however, the diagnoses in all these cases could have been made by biopsy of lesions seen on CT or FDG-PET.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between granulomas and infectious diseases seems clear. Some case series place non-Hodgkin’s lymphomas as one of the most frequent causes for the development of granulomas, with no association with LPL [ 36 , 37 ]. The fact that granulomatous lesions were not found by the diagnostic BM biopsy (with massive LPL infiltration) in contrast with its finding on the sample with only 15% infiltration suggests that the most likely etiology was systemic infection caused by Candida tropicalis.…”
Section: Discussionmentioning
confidence: 99%
“…Though the outcomes of our studies were in accordance with some previous Indian and Western literature, it must be noted that in countries such as Australia, where tuberculosis (TB) is a rare entity, causes of marrow granulomas are expected to be significantly different, as was evident from a recent publication where B cell non-Hodgkin lymphoma, sarcoidosis and autoimmune diseases were more common. 7,9…”
Section: Discussionmentioning
confidence: 99%
“…different, as was evident from a recent publication where B cell non-Hodgkin lymphoma, sarcoidosis and autoimmune diseases were more common. 7,9 In contrast to the above, Wang et al reported the highest incidence of infective aetiologies of BMGs (80/ 110 cases [72.8%]) from China. 10 TB was the most common cause (n ¼ 62), followed by fungi (n ¼ 4), typhoid or paratyphoid fever (n ¼ 3), and brucellosis (n ¼ 2).…”
Section: Diagnostic Patterns Remarksmentioning
confidence: 97%